Estudio de prefactibilidad para la instalación de una planta procesadora de paté de champiñones y nueces - Guadalupe De La Cruz, Gustavo Alonso (2020)
At the present there is a general tendency of consumers to eat based on alternative products different from meat such as vegetables, mushrooms, dried fruits and others similar. These, with the expectation of improve their health and/or their physical appearance. As a result of this increase in people’s interest in being healthier, there is also an increase in the quantity demanded of this kind of products. The following study analyzes the viability of installing a pate processing plant that has as its main inputs: mushrooms and nuts. This same will be produced from mushrooms and nuts with the addition of pepper, olive oil and salt as condiment. The product will be of pleasant taste, soft smell, creamy consistency besides of being low in calories and be characterized by being able to be consumed immediately and without any prior cooking process, also this can be consumed cold or hot. The mushrooms and nuts pate will be available in wholesale markets, supermarkets and minimarkets. This product will be directed for the socio-economic sectors A, B and C. The projected demand for 2024 will be 316,488.91 units. The presentation will be in a jar of glass and will have capacity for 150 grams of product, with a time of life of 12 months.